Komparasi Metode Always Better Control, Economic Order Quantity dan Reorder Point Untuk Analisis Pengendalian Persediaan - Widya Spalanzani; Angga Prinandar; Andi Nuraliyah; Yelly Febrina Zani (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2023)
Family Farma Pharmacy is a pharmacy that provides pharmaceutical services in Bekasi Regency. There are 50 types of medicines provided in this pharmacy, but there is no medicine grouping yet. Medicine inventory control is still done manually or by monitoring medicine stocks one by one. So there is no precise and effective calculation to determine total reorders. Therefore, the aim of this research is to grouping medicines, control medicine supplies and reorder it. The methods used are Always Better Control (ABC), Economic Order Quantity (EOQ), and Reorder Point (ROP). The findings obtained were by grouping 50 types of medicines to obtain 10 types of medicines belonging to group A, 10 types of medicines in Group B, and 30 types of medicines in Group C based on the results of the ABC method. Then the EOQ results showed that the optimal order for Cataflam 50 Mg was made for 158 strips. By reordering the Cataflam 50 Mg medicine when the medicine stock reaches 15 strips in each product inventory which still has 23 strips remaining based on the ROP results